2020
DOI: 10.1002/bjs.11616
|View full text |Cite
|
Sign up to set email alerts
|

Use of bilateral prophylactic nipple-sparing mastectomy in patients with high risk of breast cancer

Abstract: Background Nipple‐sparing mastectomy (NSM) is being performed increasingly for risk reduction in high‐risk groups. There are limited data regarding complications and oncological outcomes in women undergoing bilateral prophylactic NSM. This study reviewed institutional experience with prophylactic NSM, and examined the indications, rates of postoperative complications, incidence of occult malignant disease and subsequent breast cancer diagnosis. Methods Women who had bilateral prophylactic NSM between 2000 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…None of the 63 patients in the study by Manning who underwent risk-reducing NACsparing mastectomy (median age: 39 years) at Memorial Sloan Kettering Cancer Center developed breast cancer at a follow-up of 2.5 years [18]. In a follow-up study from the same institution, Valero and colleagues reported that at a median follow-up of 36.8 months, there had been no new breast cancer diagnoses [21]. These results confirm the initial findings reported from De Alcantara Filho et al [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the 63 patients in the study by Manning who underwent risk-reducing NACsparing mastectomy (median age: 39 years) at Memorial Sloan Kettering Cancer Center developed breast cancer at a follow-up of 2.5 years [18]. In a follow-up study from the same institution, Valero and colleagues reported that at a median follow-up of 36.8 months, there had been no new breast cancer diagnoses [21]. These results confirm the initial findings reported from De Alcantara Filho et al [20].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies met the inclusion criteria and were included in this review [13][14][15][16][17][18][19][20][21] (Figure 1). Two studies, from the same institution considered the same group of patients [20,21], and, therefore, only the one with longer follow-up [21] was included. Two studies were assessed as (Level of Evidence) LoE III and six studies as LoE IV, while the quality of the studies ranged from 5 to 7 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The longest reported follow-up of 51 months in a cohort of 26 patients undergoing prophylactic SSM implies SSM is an oncologically safe procedure in BRCA carriers [35]. Compared to SSM, NSM Despite relatively short follow-ups and retrospective nature of these reports, NSM appears to be highly preventative against breast cancer in BRCA carriers while offering superior cosmetic outcomes [37,39,40] and is as such at present the preferred option for unaffected high-risk patients in our institution.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3] The mental and physical workload for these surgeries is significant. As the nipple-sparing mastectomy procedure becomes more prevalent, 4 we cannot help but wonder the toll this will take on the surgeon.…”
Section: Pastmentioning
confidence: 99%